The Effects of Using Duolingo Towards Student’s Vocabulary Mastery (An Experiment of Junior High School Students at Omega Sains Institute) - Kusumadewi, Hermariyanti (IJET (Indonesian Journal of English Teaching), 2018)
Learning a foreign language is not so tedious and troublesome through the internet software to be the easiest platform, lots to avail and reach, such as Duolingo. Duolingo deliberately carry the concept of "playing while learning" to make it more fun and easier to use by all ages. This research aim is to find out the effects of using Duolingo towards student’s vocabulary mastery. It also expected to enable tutors to utilize electronic media such as Duolingo to support more modern and interesting teaching activities such as mobile or web-based applications. This research is an experimental research to find effects of using Duolingo (x) towards student’s vocabulary mastery (y) in controlled condition. The experimental method used is true-experimental design, the researchers used Post-test Only Control. The sampling technique used by the researcher is simple random sampling, which is the experimental class VIII consisting of 30 students, as well as the control class VIII consisting of 30 students. The result of student learning English with media Duolingo's Android Application has a positive effect compared to conventional student approaches.